A comparative study of the curricula for elementary teacher education in the Philippine Normal College and the Taipei Municipal Teachers College for Women - Lin, Yung-Shi 1938- (s.n.], 1972)
The elementary teacher education programs of the Philippine Normal College (PNC) and the Taipei Municipal Teachers College for Women (TMTCW) was analyzed and compared, with emphasis on the educational objectives and the curricula in order to formulate suggestions for a redefinition of objectives and upgrading of curricular offerings at TMTCW.